2020
DOI: 10.1002/adtp.201900208
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Trends in Nanocarbon‐Based Cardiovascular Applications

Abstract: This review aims to review the biomedical applications of nanocarbons to various cardiovascular devices including implantable scaffolds, patches, and stents against coronary artery diseases (CAD). The clinical applications of nanocarbons in cardiac tissue engineering, cardiomyocyte supporting implants, biosensors for cardiovascular biomarkers, bioimaging and monitoring of pathological conditions of CAD are addressed. In addition, the current challenges in minimizing the toxicity of nanocarbon materials and all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 212 publications
(261 reference statements)
0
2
0
Order By: Relevance
“…The engineering of reduced size electro-responsive devices, able to ubiquitously monitor the cardiovascular activity, is essential not only for the early diagnosis of cardiovascular diseases, but also to reduce healthcare costs. [130][131][132][133] However, the development of implantable systems for in vivo sensing in the cardiovascular system is extremely challenging. In fact, blood is the most complex among the biological fluids, compared, for example, to saliva or sweat, because of its highly diverse biological composition and because it is where the response to external agents is more active.…”
Section: Implantable Cardiovascular Sensorsmentioning
confidence: 99%
“…The engineering of reduced size electro-responsive devices, able to ubiquitously monitor the cardiovascular activity, is essential not only for the early diagnosis of cardiovascular diseases, but also to reduce healthcare costs. [130][131][132][133] However, the development of implantable systems for in vivo sensing in the cardiovascular system is extremely challenging. In fact, blood is the most complex among the biological fluids, compared, for example, to saliva or sweat, because of its highly diverse biological composition and because it is where the response to external agents is more active.…”
Section: Implantable Cardiovascular Sensorsmentioning
confidence: 99%
“…Even though it has been previously reported that pHEMA is a photocurable polymer with excellent biocompatibility, there is lack of information about toxicity when it is applied to biomedical devices including cardiovascular stents. [21][22][23] Resveratrol (RSL), an antioxidant loaded in pHEMA as a major drug, exerts the inhibitory effects on oxidative stress-induced endothelial apoptosis [24,25] and offers a regulatory function in the vascular expression of some genes [26,27] and enzymes [28] that expressed antiapoptotic activity in the ischemiareperfusion pathology. RSL also caused dose-dependent increases in cerebral blood flow at the concentrations of 5.65 and 14.4 ng mL −1 (0.025 and 0.061 μm), yielding its effectiveness against cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%